Clinical epidemiological profile hantavirus infection the Buenos Aires province, Argentina, during 1996-2009 - Pantozzi, Flavia; Bolzán, Andrés; Masana, Mario (Revista Chilena de Salud Pública, 2011)
ntroduction: Hantavirus infection is considered a viral zoonosis. More than 21 species have been indentified throughout the world, transmitted by different rodents, which are its natural reservoir. Until 2004, Argentina was the country with the highest incidence in South America, Buenos Aires being one of the provinces with the highest incidence in the country. Objective: The objective of this study was to analyze the clinical and epidemiological variables of the disease in the Buenos Aires Province, analyzing 14 years of historical trends (1996-2009). Materials and methods: 704 clinical-epidemiological notifications were analyzed. Serological detection of antibodies was carried out using ELISA. The variables studied were sex, age, residence according to health system district, epidemiological week (EW), incidence rate, lethality, clinical evolution, and the presence of different syndromes. Results: 622 cases (88.3%) had a laboratory serological report, 291 (46.8%) of those being positive cases or those confirmed with IgM. Analyzing clinical evolution, (194 patients included this data, 67%) 112 patients were cured y 79 died. The average age of deceased patients was 33 years. Lethality for each syndrome was: influenza 39.9%, respiratory 42.1%, renal 43.9%, hepatic 38.5%, neurological 57.1% y hematological 40%. This study contributes to knowledge of the clinical epidemiological profile of hantavirus in Buenos Aires Province, Argentina.